The Meaning of KKNI as a Paradigm Transformation of Higher Education in the Era of Globalization - Romlatul Wahidah; Buna’i (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine the meaning and role of the Indonesian National Qualification Framework (KKNI) as a paradigm shift in higher education in the era of globalization. Using a qualitative library research method, this article explores various academic sources, policy documents, and theoretical perspectives to analyze how KKNI serves as a transformative framework. KKNI aligns educational outcomes with global standards through learning outcomes-based curriculum design, level descriptors, and qualifications referencing. The study reveals that KKNI encourages competency-based education, promotes international recognition of Indonesian qualifications, and supports the development of human resources with adaptive, innovative, and globally competitive skills. In the context of higher education, KKNI becomes a strategic instrument in responding to challenges such as labor market demands, quality assurance, and cross-border mobility. The study concludes that KKNI represents a major shift from input-oriented to outcome-oriented education